2010
DOI: 10.1037/a0018720
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of means using exploratory and confirmatory approaches.

Abstract: This article discusses comparisons of means using exploratory and confirmatory approaches. Three methods are discussed: hypothesis testing, model selection based on information criteria, and Bayesian model selection. Throughout the article, an example is used to illustrate and evaluate the two approaches and the three methods. We demonstrate that confirmatory hypothesis testing techniques have more power-that is, have a higher probability of rejecting a false null hypothesis-and confirmatory model selection te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…In these papers it is often claimed that with the formulation and evaluation of informative hypotheses more powerful methods are obtained. In a few papers, some examples are provided to support this claim with numbers, e.g., [19] [20]. However, so far, no systematic study of the power of different-exploratory and confirmatory-approaches was reported and this is, therefore, the main contribution of this paper.…”
Section: Discussionmentioning
confidence: 94%
“…In these papers it is often claimed that with the formulation and evaluation of informative hypotheses more powerful methods are obtained. In a few papers, some examples are provided to support this claim with numbers, e.g., [19] [20]. However, so far, no systematic study of the power of different-exploratory and confirmatory-approaches was reported and this is, therefore, the main contribution of this paper.…”
Section: Discussionmentioning
confidence: 94%
“…Fourth, we deliberately chose not to make this paper a comparison between null hypothesis testing and the Bayesian evaluation of informative hypotheses. For such comparisons we refer the reader to Kuiper and Hoijtink (2010) or Van de Schoot et al (2011a). Moreover, we chose not to provide the reader with any guidelines or cut-off values to interpret the Bayesian output.…”
Section: Discussionmentioning
confidence: 99%
“…The main elements of this methodology are introduced below and are described in more technical detail in Appendix 2; however, for more detailed information about this method, see also Hoijtink and Boom (2008). Comparisons between more traditional ways of analyzing data and confirmatory Bayesian approaches are described in Van de Schoot and colleagues (in press) and Kuiper and Hoijtink (2010), for example. The first step in Bayesian model selection (BMS) is to specify the inequality constraints among the latent class probabilities of interest.…”
Section: Strategy Of Analysismentioning
confidence: 97%